Relationship between Self-control and Aggression in Secondary School Students - Cong, Tran Van; Hong, Nguyen Thi; Huyen, Ly Ngoc (VNU Journal of Science: Education Research; Vol 33 No 1, 2017)
This study aims to examine the relationship between self-control and aggression in secondary school students. A self-report scale and a peer-report scale were conducted on 371 students in three secondary schools in Hanoi. The results from the peer-report scale show that 25/371 students (6.74%) frequently demonstrate aggression. The analysis of the self-report scale reveals two factors: negative self-control and positive self-control from the self-control scale; and two factors: aggressive behavior and aggressive attitude from the aggression scale. The research results demonstrate negative correlation between self-control and aggression, and show that self-control is an independent variable that predicts the level and manifestation of aggression. Keywords Self-control, aggression, students, secondary school, scale References [1] Hoàng Xuân Dung, Khác biệt về giới trong hành vi gây hấn của học sinh THPT, Nghiên cứu gia đình và giới, Quyển 20- số 3 (2010) 68. [2] Lagerspetz, K. M., Björkqvist, K., & Peltonen, T., Is indirect aggression typical of females? Gender differences in aggressiveness in 11 to 12‐year‐old children. Aggressive behavior, 14(6) (1988) 403. [3] Salkind, N. J., Encyclopedia of educational psychology, SAGE publications, 2008. [4] Trần Thị Minh Đức, Game bạo lực với thanh thiếu niên - những phân tích từ góc độ tâm lý xã hội, Nhà Xuất bản Đại học Quốc gia Hà Nội, 2013. [5] Trần Thị Minh Đức, Hành vi gây hấn phân tích từ góc độ tâm lý học xã hội, Đại học Quốc gia Hà Nội, 2013. [6] Trần Thị Minh Đức, Hành vi gây hấn của học sinh phổ thông trung học, Năm 2008- 2010, Trung tâm hỗ trợ nghiên cứu Châu Á và Quỹ cao học Hàn Quốc, ĐHQGHN. [7] Denson, T. F., Capper, M. M., Oaten, M., Friese, M., & Schofield, T. P., Self-control training decreases aggression in response to provocation in aggressive individuals. Journal of Research in Personality, 45(2) (2011) 252. [8] Baumeister R. F., Exline J. J., Virtue, personality, and social relations: Self-control as the moral muscle, Journal of Personality. 67 (1999) 1165. [9] DeWall, C. N., Baumeister, R. F., Stillman, T. F., & Gailliot, M. T., Violence restrained: Effects of self-regulation and its depletion on aggression. Journal of Experimental Social Psychology, 43(1) (2007) 62. [10] Gailliot, M. T., Baumeister, R. F., DeWall, C. N., Maner, J. K., Plant, E. A., Tice, D. M., ... & Schmeichel, B. J., Self-control relies on glucose as a limited energy source: willpower is more than a metaphor, Journal of personality and social psychology, 92(2) (2007) 325. [11] Rothbaum, F., Weisz, J. R., & Snyder, S. S., Changing the world and changing the self: A two-process model of perceived control. Journal of Personality and Social Psychology, 42 (1982) 5. [12] Tangney, J. P., Baumeister, R. F., & Boone, A. L., High self‐control predicts good adjustment, less pathology, better grades, and interpersonal success. Journal of personality, 72(2) (2004) 271. [13] Baumeister, R. F., Vohs, K. D., & Tice, D. M., The strength model of self-control. Current directions in psychological science, 16(6) (2007) 351. [14] Muraven, M., & Baumeister, R. F., Self-regulation and depletion of limited resources: Does self-control resemble a muscle? Psychological bulletin, 126(2) (2000) 247. [15] Muraven, M., Tice, D. M., & Baumeister, R. F., Self-control as a limited resource: Regulatory depletion patterns. Journal of personality and social psychology, 74(3) (1998) 774. [16] Gottfredson, M. R., & Hirschi, T., A general theory of crime. Stanford, CA: Stanford University Press Tice, D. M, 1993. [17] Kim, E. J., Namkoong, K., Ku, T., & Kim, S. J., The relationship between online game addiction and aggression, self-control and narcissistic personality traits. European psychiatry, 23(3) (2008) 212. [18] Stucke, T. S., & Baumeister, R. F., Ego depletion and aggressive behavior: Is the inhibition of aggression a limited resource? European Journal of Social Psychology, 36(1), (2006) 1. [19] Đinh Thị Kim Thoa, Nguyễn Thị Mỹ Lộc, Trần Văn Tính, Tâm lý học phát triển, NXB Đại học Quốc gia Hà Nội, 2009. [20] Rosenbaum, M., A schedule for assessing self-control behaviors: Preliminary findings. Behavior therapy, 11(1) (1980) 109. [21] Higgins, G. E., Examining the Original Grasmick Scale A Rasch Model Approach. Criminal Justice and Behavior, 34(2) (2007). 157. [22] Carey, K. B., Neal, D. J., & Collins, S. E., A psychometric analysis of the self-regulation questionnaire. Addictive behaviors, 29(2) (2004) 253. [23] Yudofsky, S. C., Silver, J. M., Jackson, W., Endicott, J., & Williams, D., The Overt Aggression Scale for the objective rating of verbal and physical aggression. The American journal of psychiatry, 1986. [24] Buss, A. H., & Perry, M., The aggression questionnaire. Journal of personality and social psychology, 63(3) (1992) 452. [25] Orpinas, P., & Frankowski, R., The Aggression Scale: A self-report measure of aggressive behavior for young adolescents. The Journal of Early Adolescence, 21(1) (2001) 50. [26] Trần Văn Công, Nguyễn Thị Hồng, Lý Ngọc Huyền, Xây dựng thang đo năng lực tự kiểm soát cho học sinh trung học cơ sở tại Việt Nam, Kỷ yếu hội thảo khoa học quốc tế tâm lý học học đường lần thứ 5 - Phát triển tâm lý học học đường trên thế giới và ở Việt Nam, NXB Thông tin và truyền thông, ISBN: 978-604-80-1967-9 (2016) 358. [27] Trần Văn Công, Nguyễn Thị Hồng, Lý Ngọc Huyền, Thực trạng hành vi gây hấn ở học sinh trung học cơ sở, Kỷ yếu hội thảo Phòng chống bạo lực học đường trong bối cảnh hiện nay-Thực trạng và giải pháp, NXB ĐHQGHN, ISBN: 978-604-62-5842-1 (2016) 326. [28] Trần Văn Công, Bahr Weiss, David Cole, Bị bắt nạt bởi bạn cùng lứa và mối liên hệ với nhận thức bản thân, trầm cảm ở học sinh phổ thông, Tạp chí Tâm lý học, Số 11 (128) (2009).